الخشوع في القرآن : دلالاته وآثاره في بناء الشخصية المتميزة: دراسة تحليلية - Ainul Rasyiqah binti Sazali (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The objective of this study is to shed some light on the term 'khushu'' (humble submission) within two important points; its meaning in the Holy Quran and its effects in building a distinctive personality. There is an explanation about its meaning and its derivatives in the Quran, a clarification on its status in devotions and how it might enhance one's achievement in all aspects of life. Thus, based on the analysis of the Quranic term 'khushu'' and its derivatives, this research attempts to link between 'khushu'' and the construction of an excellent personality. Additionally, this research clarifies the practical exegesis of the Quran via the biographies of Abu Bakr al-Siddiq, 'Umar ibn al-Khattab, Abu Hurairah and Khalid ibn al-Walid, so that people may witness the models of practicing the Quran in general and 'khushu'' in particular. Several methods have been used in this research including inductive and analytical methods in studying the texts; by compiling the Quranic verses about 'khushu'' and revising them in the exegesis books, as well as studying its effects in building a distinctive personality. Among the most important findings of this research are the word 'khushu'' and its derivatives in the Quran which refer to five indications namely submission, serenity of human lives, fear, humiliaty and aridity. It affects every aspect of human life. This really shows that the application of khushu' is very important and significantly benefits humans in this life and in the Hereafter.